Breeding and testing single-cross maize hybrid QT55 in provinces in the North, South Central and Central Highlands of Vietnam - Tuong, Le Quy; Ninh, Le Van; Khoi, Nguyen Tuan; Tung, Le Quy; Thinh, Bui Bao (International Journal of Environment, Agriculture and Biotechnology, 2019)
In many places around the world, population growth and climate change have been posing huge challenges to agriculture. There are increasing demands for food products in both quantity and quality. As a result, it is essential to develop new hybrid maize varieties with high yield, quality and resistance. In this study, single-cross maize hybrid QT55 was created from a combination of two maize hybrids (D4 x D54). This hybrid maize was tested in some provinces in the North, South Central and Central Highlands of Vietnam. Study results show that in comparison with control maize cultivars, QT55 was a medium early single-cross maize hybrid (medium growth time) with the yields from 69.44 to 75.38 quintals ha-1 and ranged from 60 to 100.2 quintals ha-1 during intensive farming. Additionally, QT55 demonstrated higher resistance to stalk borer and other diseases such as the banded leaf, sheath blight and stalk rot. It is less likely to fall, cold tolerant and drought tolerant are better. Single-cross maize hybrid QT55 was best planted in Spring and Autumn-Winter crops (in Northern provinces) and Winter-Spring, Summer-Autumn crops (in South Central and Central Highlands).